THE FOREIGN LANGUAGE LEARNING ANXIETY: THE DESCRIPTIVE OF COMMUNICATION APPREHENSION, TEST ANXIETY AND FEAR OF NEGATIVE EVALUATION - Nurhayani, Nurhayani; Indriani, Fatma; Hasyimi , Ali (Universitas Muhammadiyah Prof. DR. HAMKA, 2023)
The study sought to investigate the description of learning anxiety of foreign language in three component : fear of communication apprehension, test anxiety and fear of negative evaluation. Subjects of this research were 40 students of english department and 47 students of arabic department. The learning anxiety scale is used to collect the data. It is adapted based on learning anxiety scale of FLCAS (Foreign Language Classroom Anxiety Scale) developed by Horwitz et al in 1986, consisting of 33 items. Analysis of descriptive by using SPSS 25 as applied to analyze the data. The result of the analysis shows that foreign language learning anxiety among English department students are 24.4 % high, 73,2% medium and 2,4% low. The foreign language learning anxiety among Arabic department students are 17 high, 78,7 % medium and 4,3% low. The research found the anxiety of communication apprehension among students of English department are 36.6% high, 61% medium and 2.4% low. The anxiety of communication apprehension among students of Arabic department are 21.3% high, 76.6 % medium and 2.1 % low. The aspect of test anxiety among students of English department are 4.9% high, 75.6 medium and 19.5 low. The result of anxiety among students of Arabic department are are 10.6% high, 85.1% medium and 4.3% low. The aspect of Fear of negative evaluation among university students of English department are 39% high, 58.5% medium and 2.4% low. The aspect of Fear of negative evaluation among students of Arabic department are 31.9% high, 63.8 % medium and 4.3% low. Keywords: learning anxiety, foreign language learning, communication apprehension, test anxiety, negative evaluation